Corneal ulcer: an epidemiological, microbiological and clinical study of cases attending Assam medical college and hospital, Dibrugarh, India - Baruah, Mamoni; Das, Rajiv Kumar; Agarwalla, Vijaya; Basyach, Pranami (International Journal of Research in Medical Sciences, 2020)
Background: Corneal ulcer is one of the important ophthalmic conditions causing significant morbidity especially in the developing countries. This study was carried out to evaluate the common etiological agents, predisposing factors, age, gender and occupational distribution and to study the clinical features and management of all corneal ulcers. Methods: A total of 50 cases of corneal ulcers who attended the Ophthalmology outpatient department (OPD) of Assam medical college and hospital, Assam, India, over a 6 months period were included in the study. A detailed history was taken and examination done as per the proforma. Microscopy and culture were performed on all corneal specimens obtained. Results: Corneal ulcers were common in 3rd to 5th decades of life with Male to Female ratio of 1.3:1. Majority of patients were farmers or hired agricultural workers. Ocular trauma was the major predisposing factor in majority of cases (32%). Out of 50 cases, 31 (62%) were culture positive. 19 were bacterial isolates and 12 were fungal isolates. All patients were treated according to standard treatment protocol and majority (95.5%) patients responded well to treatment. Conclusions: This study has revealed that suppurative corneal ulcers are caused by both bacterial and fungal agents with bacterial preponderance in this geographical area. Early and accurate diagnosis and intensive treatment is the need of hour for saving the eye and preventing the catastrophe of lifelong blindness.